The state of Namibia's concrete infrastructure – A comparative study of Walvis Bay, Swakopmund, Arandis and Usakos towns - Chirembo, Kondwanie Frank (Department of Civil Engineering, 2021)
In Namibia, the design and construction specification of concrete (for durability) follows the traditional method of prescribing parameters which over time are believed to produce durable concrete. These parameters include concrete exposure definition, cover, concrete strength, concreting materials and concreting methods. International research has shown that some of these parameters do not have a direct relationship with the durability of “As-built” concrete structures; rather that concrete structures can be designed and constructed to meet specific performance levels of the environment they are built in. In this case, testing of the concrete during design, construction and post-construction (to set acceptable limits and confirm adherence to the limits) becomes part of the process. This project was undertaken to look at how concrete practices (design and construction specification) followed in Namibia have impacted on the durability of concrete structures. To achieve the objective, the approach followed included; first assessing the prevailing concrete conditions (in different areas across Namibia), reviewing current concrete design and construction specifications used in the industry and finally assessing practitioner knowledge on performance-based concrete design and construction specification. Concrete infrastructure in four towns (Walvis Bay, Swakopmund, Arandis and Usakos) were inspected and deteriorations recorded. From these inspections, an evaluation of the causes of the deterioration was undertaken. A comparison was undertaken on the prevalence of different deterioration mechanisms in the four areas. Design standards, for durability, followed by structural engineers in Namibia were reviewed including specifications demanded by different infrastructure developing agencies. The limitations of these were highlighted. Interviews and observations were undertaken with structural engineering practitioners on knowledge of design for concrete durability. From the information collected, the comparison and assessment it was concluded that there is a need to revise the concrete design and construction specification to ensure concrete performs better against the most significant risk to concrete service life; damage due to reinforcement corrosion. Concrete specifications need to have measurable durability parameters which can be used for acceptance of concrete works besides compressive strength. The Namibia Port Authority (NAMPORT) has taken a step in this direction with the development of concrete construction specifications which have adopted the South African Durability Index method as part of the concrete acceptance criteria. Challenges encountered (by NAMPORT) include lack of testing equipment and a lack of knowledge by material testing engineers. With Namibia having the challenge of not having a national concrete construction standard, it is further recommended that major infrastructure developers (Namibia Water Authority, NAMWATER, and Roads Authority, RA) should lead in adoption of similar specifications to the NAMPORT ones. As most engineers in Namibia undertake works for either NAMWATER or RA, the industry will be more willing to undertake the training of engineers on the South African durability index method as it will make economic sense. The training is recommended to include training of laboratories offering material testing services in Namibia.